2015
DOI: 10.1021/acs.chemrestox.5b00392
|View full text |Cite
|
Sign up to set email alerts
|

CADRE-SS, an in Silico Tool for Predicting Skin Sensitization Potential Based on Modeling of Molecular Interactions

Abstract: Using computer models to accurately predict toxicity outcomes is considered to be a major challenge. However, state-of-the-art computational chemistry techniques can now be incorporated in predictive models, supported by advances in mechanistic toxicology and the exponential growth of computing resources witnessed over the past decade. The CADRE (Computer-Aided Discovery and REdesign) platform relies on quantum-mechanical modeling of molecular interactions that represent key biochemical triggers in toxicity pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
89
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(95 citation statements)
references
References 45 publications
5
89
1
Order By: Relevance
“…Another approach combining a linear QSAR method with an expert-curated set of rules has been implemented in the CADRE-SS model for predicting the skin sensitization potency of compounds (Kostal and Voutchkova-Kostal 2016;ToxFix). The three-class categorical hybrid model consists of three modules describing different steps in the sensitization process.…”
Section: Hybrid In Silico Modelsmentioning
confidence: 99%
“…Another approach combining a linear QSAR method with an expert-curated set of rules has been implemented in the CADRE-SS model for predicting the skin sensitization potency of compounds (Kostal and Voutchkova-Kostal 2016;ToxFix). The three-class categorical hybrid model consists of three modules describing different steps in the sensitization process.…”
Section: Hybrid In Silico Modelsmentioning
confidence: 99%
“…Another study proposed a hierarchical model where skin permeability is evaluated using Monte Carlo simulations, chemical reactive centers are determined with expert rules, and protein reactivity is predicted by the means of quantum-mechanical modeling. 61 The authors reported conspicuously impressive results for predicting skin sensitization of an external set mostly composed by LLNA, Buehler’s test, and GMPT data: sensitivity as high as 87%, specificity as high as 100%, and balanced accuracy of 93%, which exceeded the reported 67 concordance of 89% between LLNA and GMPT.…”
Section: Introductionmentioning
confidence: 93%
“…Using computer models to accurately predict toxicological outcomes is an important task, but current in silico toxicology is now based on advances in mechanotoxicity and predictive models that have grown remarkably in computing resources over the last decade. The integrated computer-aided discovery and redesign (CADRE) platform is used as a model for key molecular interactions in the toxic pathway [62]. CADRE offers distinct advantages over the primary screening of chemicals and suggests that it could be performed as an alternative in silico tool that is allowed in legislative programs [62].…”
Section: Advances In Toxicology Prediction For Occupational Healthmentioning
confidence: 99%